Mapping Global Research Trends in Interactive Learning Media: A Bibliometric Analysis of Scopus Publications (2021–2025) - Razilu, Zila; Sulfasyah, Sulfasyah; Nappu, Syamsiarna (PPSDP International Journal of Education, 2025)
This study maps and analyzes global research trends in interactive learning media from 2021 to 2025, with a focus on emerging technologies and pedagogical shifts. A quantitative bibliometric method was used, drawing data from the Scopus database and analyzing it through bibliometric mapping and visualization techniques. The results show a steady rise in publication output and expanding collaborative networks across institutions and countries. Thematic evolution highlights the increasing prominence of mobile learning, artificial intelligence integration, and immersive digital environments. This study provides a novel and comprehensive mapping of post-pandemic research patterns and identifies clusters that connect technology design with learning effectiveness. Practically, the findings offer data-driven insights for educators, policymakers, and developers to strengthen future digital learning strategies. The study also reinforces the theoretical foundations of educational technology and supports evidence-based innovation in interactive and adaptive learning models.